O sytuacji komunikacyjnej współczesnego słuchowiska – wybrane zagadnienia - Bachura, Joanna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
This article focuses on chosen elements of the communication situation of radio-play. Particularly, the sender and the author are discussed. Attention is paid to the institutional nature of the art of radio-play, as well as the problem of the authorship. However, the listener is also essential in the context of a complete description of the audio culture text, as underlined in several other publications.